The preconditions for increasing phosphorus recycling from sewage systems in Sweden : a study of factors influencing Swedish farmers´ willingness to use phosphorus fertilizers produced from sewage sludge - Edholm Widén, Jesper (SLU/Dept. of Biosystems and Technology (from 130101), 2019)
The Swedish government (2018) is currently investigating options for prohibiting direct application of sewage sludge on arable fields and replace it with techniques capable of precipitating phosphorus from sewage sludge and turn it into refined phosphorus fertilizing products. The investigation is part of the government´s ambition to increase the recycling rate of phosphorus available in sewage sludge and thus turn the sludge into a greater agricultural resource than it is today (ibid). The success of refined phosphorus fertilizers is primarily contingent on farmers´ willingness to use them, making the factors influencing this willingness crucial to be aware of. However, these factors are not explicitly mentioned as being taken into consideration in the government´s investigation (ibid), and no previous research exists on this topic. For this reason, this thesis has focused on investigating the factors influencing Swedish farmers’ willingness to use refined phosphorus fertilizers produced form sewage sludge. It has done so by conducting semiBstructured interviews with nine Swedish conventional farmers. Their answers have been analysed using inductive thematic analysis. The analysis identified three themes, or factors, influencing farmers’ willingness to use refined phosphorus fertilizers produced from sewage sludge; (1) Scientific understanding about the products, (2) Features of the products, and (3) Price of the products.